STUDENT STUDENTS’ ACADEMIC PROGRESS AND PARENTAL INVOLVEMENT AT ELEMENTARY LEVEL: A CASE STUDY OF GRADE 8 (GIRLS) OF FRONTIER SCIENCE ACADEMY (FSA) (Khairulummah, 2023)
Parents who   spend time with their children at home and assist them in study bring  positive results in their kid’s academic performance. Therefore, for effective learning there is a need of active contact between the school instructional practices and  leaners families. This study hypothesize that there is a positive correlation between active participation of parents   and children educational achievement.  in In the study Parental Involvement has been chosen as an independent variable and Academic  Performance   as the dependent variable. Indicators of Parental Involvement are, assistance to student, discussion, support in homework and contact with instructor. Academic Performance represented in   higher grades, test scores, and better school attendanceMethodology employed is qualitative, data collection mainly draw from parents of the 137 students (girls) through personal interview and questionnaire,  registered at school, the Frontier Science Academy Hayatabad, Peshawar, of Khyber Pukhtun khwa. Data was analyzed through SPSS   percentage frequency distribution and produced findings and conclusions. Grade 8 female students were taken as respondents.
Keywords: grade 8, elementary school, parental involvement, academic achievements